Measuring decrement in change-of-direction speed across repeated sprints in basketball: novel vs. traditional approaches - Scanlan, A. T.; Madueno, M. C.; Guy, J. H.; Giamarelos, K.; Spiteri, T.; Dalbo, V. J. (The Journal of Strength and Conditioning Research, 2021)
Approaches to quantify decrement in change-of-direction speed during repeated sprints in basketball players have traditionally used total performance time, which is strongly influenced by linear speed. The purpose of this study was to compare performance decrement across change-of-direction sprints using total performance time and a novel approach that better isolates change-of-direction speed, termed change-of-direction deficit (CODD). Semiprofessional basketball players (N = 8; 19.9 ± 1.5 years; 183.0 ± 9.6 cm; 77.7 ± 16.9 kg) completed 12 × 20-m change-of-direction sprints (Agility 5-0-5 trials) with 20-second recoveries between each sprint. Agility 5-0-5 performance time was taken as the duration to cover 5 m immediately before and after (10 m in total) a 180° directional change. Change-of-direction deficit was calculated as the difference between mean 10- and 20-m split time determined during reference 20-m linear sprints in a separate session and Agility 5-0-5 time in each sprint. Performance decrement was calculated for each approach as: ([total time/ideal time] × 100) - 100. Comparisons between approaches were made using a paired-sample t-test, effect size analyses, and magnitude-based inferences. A significantly greater (P < 0.001; effect size = 2.16, very large; almost certainly higher) performance decrement was apparent using CODD (5.99 ± 1.88%) than Agility 5-0-5 performance time (2.84 ± 0.84%). The present findings indicate that change-of-direction speed measured with CODD shows promise in providing different insight and deteriorates more than total performance time during repeated sprints in basketball players. Change-of-direction deficit has potential to better isolate decrements in change-of-direction speed across repeated sprints compared with total performance time.